Due diligence and good faith in reference to the rulings Court of Justice of the European Union and polish administrative courts - Michalak, Monika (Studia Iuridica Toruniensia, 2017)
This article discusses an issue of due diligence and good faith in reference to tax on goods and services (value added tax in accordance with EU regulations) considering the rulings Court of Justice of the European Union and Polish administrative courts. The Court of Justice of the European Union followed by Polish administrative courts pointed out that due diligence as well as good faith pose as a basis for due tax deduction while speaking of tax on goods and services. According to many rulings, the right for tax deduction cannot be denied a tax payer who meets all of the conditions including due diligence and good faith thus shall have this right granted. In simple terms, good faith means that a tax payer performs his/her tax duties in a just and honest manner. Due diligence, on the other hand, consists in entrepreneur’s making sure that all of the business transactions are reliable and his/her not taking part or being a part of any tax fraud. This article deals only with fighting against tax frauds and will not touch upon the mechanisms of tax carrousels.